Enhancing Vocational Graduate Employability: The Roles of ‎Teachers' Pedagogical Competence and School–Industry ‎Partnerships in Kendal Regency - Santi Larasati; Rosalina Br. Ginting; Lilik Ariyanto (Yayasan Darussalam Bengkulu, 2026)
Vocational education plays a strategic role in preparing graduates to meet labor market demands. However, despite the industrial potential of Kendal Regency, the employability of vocational high school graduates remains a challenge due to job mismatch, limited entrepreneurial opportunities, and difficulties in aligning educational outcomes with industry needs. This study examines the influence of teachers' pedagogical competence and school–industry partnerships on vocational high school graduate employability. A quantitative ex post facto correlational design was employed involving 216 teachers from public vocational high schools in Kendal Regency, Indonesia, selected through purposive sampling. Data were collected using structured questionnaires and analyzed using simple and multiple linear regression with IBM SPSS Statistics version 27. Prior to hypothesis testing, normality, linearity, heteroscedasticity, and multicollinearity tests were conducted. The findings revealed that teachers' pedagogical competence had a positive and significant effect on graduate employability (R² = 0.363, p < 0.001), while school–industry partnerships also showed a positive and significant effect (R² = 0.169, p < 0.001). Simultaneously, both variables significantly influenced graduate employability (R = 0.617; R² = 0.381; F = 65.60; p < 0.001), indicating that 38.1% of the variance in graduate employability was explained by the combined contribution of the two predictors. Teachers' pedagogical competence emerged as the stronger predictor. These findings suggest that strengthening teachers' pedagogical competence and enhancing sustainable school–industry partnerships are essential strategies for improving vocational graduate employability and supporting better alignment between vocational education and labor market needs.